PRODUCTIVITY ANALYSIS OF EXCAVATOR HEAVY EQUIPMENT IN SAND MINING AT PT MITRA PASIR SILIWANGI - Alvarizzy, Muhammad Harry; Lusiana, Lusiana; Nuh, Safruddin M. (Jurnal Teknik Sipil, 2024)
Heavy equipment, including mining activities, is a crucial resource often required in project work. PT Mitra Pasir Siliwangi in Sintang Regency uses heavy equipment from the excavator to support sand mining operations. This study aims to determine the productivity value of heavy equipment in sand mining activities, specifically the Kobelco SK 130-8 Excavator. The productivity value is obtained from field data collected over seven days and compared with the planned productivity per the company's planning. The study results show that the planned productivity value for the heavy equipment is 91.58 m ³/hour, while the actual field productivity value is 65.89 m ³/hour. Therefore, it is concluded that using the Kobelco SK 130-8 Excavator for sand mining has a lower field productivity value than the planned productivity. This discrepancy is due to several factors, such as data recording errors in the field and frequently idle equipment (the machine is running but not performing mining activities).